1988
DOI: 10.1111/j.1476-5381.1988.tb11442.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of muscarinic receptor on cholinergic nerves and atrial cells of chicken and guinea‐pig hearts

Abstract: 1 Electrically driven chicken and guinea-pig atria were used to investigate the negative inotropic effects of the muscarinic agonists methacholine and acetylcholine (ACh). The release of ACh from isolated hearts into the perfusate in response to (preganglionic) vagal or (pre-and postganglionic) field stimulation was bioassayed on the guinea-pig ileum or determined by labelling with ['H]-choline. (Pz) and atropine were 40 and 5.4 nmol -'in chicken atria and 330 and 3.5 nmol '-', respectively, in guineapig atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Presynaptie M 1 -receptors have also been found in ehieken heart (Jeck et al, 1988), different guinea-pig and rat brain areas (Belleroehe and Gardiner, 1985;Marehi et al, 1986;Williams and Constanti, 1988) as weil as in guinea-pig and rat small intestine (Mieheletti et al, 1988;Sehwörer and K.ilbinger, 1988). However, it remains to be elueidated whether all these presynaptie musearlnie reeeptors are pharmacologieally identieal or whether they belang to different M 1 -reeeptor subclasses.…”
Section: Discussionmentioning
confidence: 99%
“…Presynaptie M 1 -receptors have also been found in ehieken heart (Jeck et al, 1988), different guinea-pig and rat brain areas (Belleroehe and Gardiner, 1985;Marehi et al, 1986;Williams and Constanti, 1988) as weil as in guinea-pig and rat small intestine (Mieheletti et al, 1988;Sehwörer and K.ilbinger, 1988). However, it remains to be elueidated whether all these presynaptie musearlnie reeeptors are pharmacologieally identieal or whether they belang to different M 1 -reeeptor subclasses.…”
Section: Discussionmentioning
confidence: 99%
“…Such receptors have previously been described in the cardiac nerves in the rat (Wetzel & Brown, 1985) and in the guinea-pig (Jeck et al, 1988). Blockade of these receptors by gallamine would increase transmitter output from the vagus nerves and increase the concentration of antagonist required to inhibit vagallyinduced bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the guinea-pig is the only species in which M2 receptors have been demonstrated in both pulmonary (Fryer & Maclagan, 1984) and cardiac (Jeck et al, 1988) parasympathetic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity of chick cardiac receptors for pirenzepine has been observed repeatedly (Brown et al, 1985;Lindmar & Loffelholz, 1987;Jeck et al, 1988;Choo et al, 1988;Lazareno et al, 1990;Tietje & Nathanson, 1991), although low affinity was found by Sorota et al (1986). (2) The M2-like sites in chick heart have a slightly lower Kd for NMS than the M4-like population, while in mammalian tissues, the affinity of M4 receptors for NMS is higher than that of M2 receptors (Waelbroeck et al, 1990;Lazareno et al, 1990).…”
Section: Effect Of Alcuronium On the Dissociation Of [3h]-nmsmentioning
confidence: 93%
“…They appear similar to the Ml subtype because of their high affinity for pirenzepine (Brown et al, 1985;Lindmar & Loffelholz, 1987;Jeck et al, 1988), but the pattern of affinities of other ' Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%